PERLINDUNGAN HUKUM BAGI MASYARAKAT TERHADAP PENCEMARAN UDARA AKIBAT INDUSTRI PELEBURAN LIMBAH DAUR ULANG ALUMINIUM - Pratistita, Made Wipra; Triadi, Irwan (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
Aluminum is a metal that is used as a basic material for making human equipment products. Aluminum products that are not used often become rubbish or waste that can be recycled. Recycling of aluminum waste is carried out by smelting. The aluminum smelting process of course produces gas emissions which, when released into the wild, have an impact on reducing the quality of clean air. This research discusses the extent to which legal protection can be provided for the behavior of the aluminum smelting industry which disposes of waste gas from its smelting into the wild when viewed from statutory regulations. In this research the author uses normative legal research methods using legal sources from primary legal materials in the form of environmental law legislation and secondary legal materials in the form of books and articles regarding the management of hazardous and toxic waste. The conclusion obtained in this paper is that the disposal of gas resulting from smelting aluminum waste that exceeds air quality standards can be subject to law enforcement processes based on applicable statutory provisions.